Survivorship and risk factors for revision of metal-on-metal hip resurfacing – a long-term follow-up study - Edwards,T (Bone & Joint Open, 2023)
AimsMetal-on-metal hip resurfacing (MoM-HR) has seen decreased usage due to safety and longevity concerns. Joint registries have highlighted the risks in females, smaller hips, and hip dysplasia. This study aimed to identify if reported risk factors are linked to revision in a long-term follow-up of MoM-HR performed by a non-designer surgeon.MethodsA retrospective review of consecutive MoM hip arthroplasties (MoM-HRAs) using Birmingham Hip Resurfacing was conducted. Data on procedure side, indication, implant sizes and orientation, highest blood cobalt and chromium ion concentrations, and all-cause revision were collected from local and UK National Joint Registry records.ResultsA total of 243 hips (205 patients (163 male, 80 female; mean age at surgery 55.3 years (range 25.7 to 75.3)) with MoM-HRA performed between April 2003 and October 2020 were included. Mean follow-up was 11.2 years (range 0.3 to 17.8). Osteoarthritis was the most common indication (93.8%), and 13 hips (5.3%; 7M:6F) showed dysplasia (lateral centre-edge angle < 25°). Acetabular cups were implanted at a median of 45.4° abduction (interquartile range 41.9° - 48.3°) and stems neutral or valgus to the native neck-shaft angle. In all, 11 hips (4.5%; one male, ten females) in ten patients underwent revision surgery at a mean of 7.4 years (range 2.8 to 14.2), giving a cumulative survival rate of 94.8% (95% confidence interval (CI) 91.6% to 98.0%) at ten years, and 93.4% (95% CI 89.3% to 97.6%) at 17 years. For aseptic revision, male survivorship was 100% at 17 years, and 89.6% (95% CI 83.1% to 96.7%) at ten and 17 years for females. Increased metal ion levels were implicated in 50% of female revisions, with the remaining being revised for unexplained pain or avascular necrosis.ConclusionThe Birmingham MoM-HR showed 100% survivorship in males, exceeding the National Institute for Health and Care Excellence ‘5% at ten years’ threshold. Female sex and small component sizes a